Peningkatan Motivasi Dan Hasil Belajar Siswa Dengan Menggunakan Media Komik (Ptk Bagi Siswa Kelas Viii Semester Genap Mts Negeri Filial Pulutan Tahun - Efriani, Dihan Utama, Masduki S.Si., M.Si (2016)
The purpose of this study is to describethe increase in student motivation through the medium of comics in class VIII B MTsN Filial Pulutan, boyolali. This research is a classroom action research. Class VIII B as the recipient of the action and the math teacher as giver action. Data colletion methods used are observation, field notes, test and documentation. Data analysis technique used is the process of data analysis, data presentation, and data verification. The result of the study showed an increase in student motivation can be seen from : 1) student who follow the spirit of the learning prosess as many as 13 student (81.25%); 2) student were able finished chores or school assigments as many as 15 student (93,75%). With the increased student motivation, the result of student learning is increasing, the average value above the KKM. This it can be concluded that the medium of comics in mathematics learning can increase student motivation and learning outcomes.